2006
DOI: 10.1080/09297040600876311
|View full text |Cite
|
Sign up to set email alerts
|

Memory and Executive Functions in Pediatric Chronic Kidney Disease

Abstract: This study examined the memory and executive functioning of children and adolescents with chronic kidney disease (CKD). The sample included 20 children and adolescents with CKD ranging in age from 7.50 to 19.04 years (M = 13.41, SD = 3.20). Intellectual function for the group was within the low average to average range (M = 89.32, SD = 14.80). Of the participants with CKD, 12 were receiving maintenance dialysis therapy at the time of testing and 8 were managed with conservative therapy. Healthy controls were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 38 publications
3
54
0
Order By: Relevance
“…When individual patients were examined, however, there was a large percentage of children who evidenced risk for dysfunction. This was especially noteworthy for the parent ratings of executive functioning, where percentages ranged from 27% to 40%, and would be consistent with previous work showing executive dysfunction in mixed-severity samples of children with CKD using laboratory assessments (19). Although executive impairments are certainly not unique to kidney disease, their appearance in children with mild-tomoderate CKD severity is noteworthy, particularly given that this disease undoubtedly will worsen over time.…”
Section: Discussionsupporting
confidence: 67%
“…When individual patients were examined, however, there was a large percentage of children who evidenced risk for dysfunction. This was especially noteworthy for the parent ratings of executive functioning, where percentages ranged from 27% to 40%, and would be consistent with previous work showing executive dysfunction in mixed-severity samples of children with CKD using laboratory assessments (19). Although executive impairments are certainly not unique to kidney disease, their appearance in children with mild-tomoderate CKD severity is noteworthy, particularly given that this disease undoubtedly will worsen over time.…”
Section: Discussionsupporting
confidence: 67%
“…A number of studies have identified lower nonverbal intelligence quotient (IQ) and motor performance in children with kidney disease compared with healthy age-matched controls (6)(7)(8)(9)(10)(11). Some have found no significant differences in memory (verbal and nonverbal) between children with and without CKD (11).…”
Section: Introductionmentioning
confidence: 99%
“…Children with CKD show impairments in attention, memory, executive functioning, language, visual-spatial abilities, and academic achievement (1)(2)(3)(4), while adults with CKD have increased risk of cognitive impairment and dementia (5)(6)(7)(8)(9). Impaired cognitive function has been linked to poor treatment adherence in multiple disease states, including kidney transplantation (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%